PEMODELAN SPASIAL BAHAYA BANJIR ROB BERDASARKAN SKENARIO PERUBAHAN IKLIM DAN DAMPAKNYA DI PESISIR PEKALONGAN - Muh Aris Marfai (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractTidal flood is predicted to be more severe in the future because of sea level rise due toglobal warming. Purposes of the study are: 1) identify spatial distribution of tidal floodhazard in Pekalongan coastal area; 2) identify environmental impacts of tidal flood inPekalongan coastal area; and 3) formulate coastal management based on spatialdistribution analysis and tidal flood impacts in Pekalongan. Flood analysis in coastalarea was conducted by flood hazard mapping using GIS (Geographic Information System).Flood hazard mapping was developed by integrating GIS operation with DEM (DigitalElevation Model), level of inundation and iteration process. Tidal flood inundation scenariowas generated based on highest tides and sea level rise scenario by IPCC 2007, level ofinundation reached up to 135 mm. Results of this study showed that settlement and irrigatedpaddy fields are the widest inundated area by tidal flood. Tidal flood provides seriousenvironmental impacts such as infrastructure damage, agriculture and aquaculture landdamage, and soil and water pollution. Infrastructure damages include road, settlementsand sanitation.